Reducing the time from basic research to innovation in the chemical sciences : a workshop report to the Chemical Sciences Roundtable (Online access: NCBI NCBI Bookshelf., 2003)
Innovation, the process by which fundamental research becomes a commercial product, is increasingly important in the chemical sciences and is changing the nature of research and development (R & D) efforts in the United States. The workshop "Reducing the Time from Basic Research to Innovation in the Chemical Sciences" was held in response to pressures to speed the R & D process and to rapidly evolving patterns of interaction among industry, academe, and national laboratories. The aim of the workshop was to identify and discuss approaches that might speed the innovation process by which basic research leads to innovation. The papers in this volume are the authors' own versions of their presentations. The discussion comments were taken from a transcript of the workshop.